Common Predictive Factors of Social Media Addiction and Eating Disorder Symptoms in Female College Students: State Anxiety and the Mediating Role of Cognitive Flexibility/Sustained Attention - He, Zhonghua; Li, Mingde; Liu, Chanjun; Ma, Xiaoyue (Frontiers in Psychology, 2022)
The aim of this study was to investigate the common predictive factors between social media addiction and eating disorder symptoms in a group of female college students. A total of 216 female college students completed the behavioral measures of cognitive flexibility and sustained attention, and the questionnaires of anxiety, social media dependence and eating disorder. The results of this study indicate that social media addiction is significantly correlated with eating disorder symptoms. Structural equation modeling was used to test the model in which state anxiety, cognitive flexibility and sustained attention predicted social gain and eating disorder symptoms, and the results confirmed the mediating role of cognitive flexibility and sustained attention between state anxiety and social media addiction/eating disorder symptoms in female college students. The findings revealed that in young female group, state anxiety was related to social media addiction and eating disorder symptoms through cognitive flexibility and sustained attention. These proposals reflect the significance of improving cognitive flexibility/sustained attention and reducing state anxiety to prevent eating disorder symptoms and social media addiction in female college students.